Takhrij and Syarah Hadith of Agrotechnology: Efforts to Conserve the Earth with Reforestation - Sevi Sevtiani Hamdani; Wahyudin Darmalaksana; Ahmad Taofik (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith of the Prophet Muhammad SAW regarding the nobility of farming. The method used in this research is through the approach of takhrij and sharah hadith agrotechnology. Results and discussion of this research is that the Prophet Muhammad SAW encouraged his people to carry out farming activities and have been carried out until now. The conclusion of this study is that environmental conservation efforts can be done by planting crops.